Epidemiology of Moniliophthora roreri: a field study in the Atlantic Zone of Costa Rica - Tazelaar, C.J. (Centro Agronómico Tropical de Investigación y Enseñanza (CATIE), Turrialba (Costa Rica). Atlantic Zone Programme Agricultural University Wageningen, Wageningen (Países Bajos) Ministerio de Agricultura y Ganadería, San José (Costa Rica), 2014)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica),1991